Genome evolution of endosymbiotic bacteria in blood-sucking insects - Říhová, Jana (Jihočeská univerzita, 2023)
The research on insect-bacteria symbiosis is experiencing a rapid burst leading to the identification of much higher complexity and dynamics of the insect-bacteria associations than ever before envisaged. The generally accepted concept of obligate bacterial symbionts as providers of essential compounds (vitamins, aminoacids) has been further developed into the framework of microbiomes, i.e. communities of microorganisms associated with the host. The majority of the knowledge has been derived from plant sap-feeders, while data on blood-feeding insects remain fragmented and even inconsistent. In this thesis, we employ amplicon, genomic and in-vivo approaches to investigate several symbiotic systems of obligate blood-feeders and address the following questions: What is the diversity of symbiotic bacteria in our studied systems? What are the metabolic capacities of these symbionts? What is the role of symbionts in the biology of their hosts? What are the possible sources of bacteria prone to establish symbiosis with obligate blood-feeders? Where these symbionts reside in the host´s body? What is the coevolutionary pattern of these bacteria with their hosts? As an answer to these questions, I present the results detailed in the course of this thesis, which are preceded by a comprehensive introduction to the studied topics and wraps up with a summary of the main results.
Genome evolution of endosymbiotic bacteria in blood-sucking insects
Keywords: symbiotic bacteria; obligate blood-feeders; microbiome; amplicon sequencing; whole-genome sequencing; metaboic capacities